Stephen Hawking : a memoir of friendship and physics - Mlodinow, Leonard, 1954- (Pantheon Books, 2020)
"A memoir from the author of SUBLIMINAL and THE DRUNKARD'S WALK revealing his relationship with renowned physicist Stephen Hawking as both a fellow scientist and a friend"--